Educação ambiental e queimadas: a construção de conceitos no ensino de ciências para formação de sujeitos ecológicos - CORRÊA, Nilton da Silva (2020)
The wear and tear on the environment triggered by contemporary society's actions and behaviors boosted the political, economic and educational paradigms for the need to train individuals with ecologically correct attitudes and behaviors, based on sustainable assumptions. When referring to Science Education and Environmental Education, the science teacher as the mediator of a teaching process, plays an extremely important role in stimulating actions with ecologically acceptable ideas. In this sense, the present dissertation approached a discussion about Environmental Education, fires and the construction of knowledge in science teaching for the formation of ecological subjects. The theoretical frameworks used to guide the discussions were based mainly on Angotti (2011); Carvalho (2012); Cachapuz (2011); Chassot (2014); Delizoicov (2011); Leff (2015); Laurel; Torres (2014); Segura (2001) among others. The research is classified, according to the methods employed, as a case study, supported by Gil (2017), Bardin (2011), Franco (2009). The study used the perspective of the qualitative research approach whose data collection took place in seventeen elementary schools, rural area of the municipality of Codó / M. It had as a research subject, Science teachers with whom questionnaires and interviews about the concept of AE and Queimadas were applied in the city of Codó / MA. The results showed that teachers have more theoretical than practical actions on local environmental problems, as well as working with traditional and reduced pedagogical instruments regarding the implementation of environmental education in the school space. The category that presented itself in greater quantity in relation to the units of meanings taken from the teachers' conceptions in response to the focus of this investigation converged towards the promotion of environmental awareness among students. It was also noticed that it has over burns is almost invisible as a pedagogical action among teachers. The product of this research was configured in a paradidactic that sought to contribute in the pedagogical work of the science teacher to the problem of burning in the city of Codó / Maranhão.